RISK MANAGEMENT IN SARAWAK ROAD CONSTRUCTION PROJECTS - Carolina, Jolson Ng (Universiti Malaysia Sarawak, 2023)
Construction projects in Sarawak are associated with various levels of risk. A risk is an unexpected event or consequence that might positively or negatively influence at least one project aim if it occurs. Furthermore, this project typically involves substantial risk due to the large geographic distribution area and the possibility of underground conditions. The primary purpose of this study is to discover the significant risk factors impacting road construction projects in Sarawak and current risk management practices performed by the contractors, including techniques. The scope of the study is on any road construction projects in the Sarawak area to identify the risk factors that may occur in every project. This study is a quantitative study, which identifies risk factors through a questionnaire survey; and is distributed to the contractors involved in the construction area. The data of the study was analysed using IBM SPSS STATISTICS 29. Descriptive Analysis and Relative Importance Index (RII) was used to analyze the data. The findings of the study shows that the most significant risk in road construction projects is weather condition. Furthermore, the most common risk management techniques utilized by contractor are Checklist Monitoring, Probability-Impact Matrix, and Risk Mitigation.